(untitled) (Journal of the College of Basic Education, 2025)
The study aimed to identify the effect of the idea filtering strategy on the pivotal thinking in mathematics for intermediate school students. To achieve the research objective, the null hypothesis was formulated, which states: "There is no statistically significant difference at the significance level (0.05) between the average scores of the experimental group students who study mathematics according to the idea filtering strategy and the scores of the control group students who study the same subject in the usual way in the pivotal thinking test in mathematics." The experimental research method with partial control of the two equivalent groups was used. The research sample was randomly selected from the second intermediate grade students from Al-Fawz Girls School, whose number reached (66) students after statistical exclusion. The pivotal thinking test was prepared, which consisted of (24) multiple-choice test items. After ensuring the validity and reliability of the test and completing the teaching of the experimental group according to the idea filtering strategy and the control group according to the usual method. The pivotal thinking test was applied to the female students in the research sample and the results showed a statistically significant difference in favor of the experimental group. In light of the results, the researcher recommends using the idea filtering strategy in teaching mathematics due to the interaction this strategy creates within the classroom, as it encourages learners to put forward all ideas revolving around mathematical topics and choose the best of those ideas according to specific criteria and foundations. Accordingly, she suggests conducting a study to determine the effect of the idea filtering strategy on achievement and higher-order thinking .